Immunogenicity Assessment on Clinical Trials of SARS-CoV-2 Vaccines - Munawaroh Fitriah; Jusak Nugraha (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2022)
Various strategies for dealing with COVID-19 have been carried out since the WHO declared COVID-19 as an international health emergency. One of the preventive strategies is the development of vaccines. Various vaccines have been developed worldwide. As of April 13, 2021, there were 184 vaccine candidates in the pre-clinical phase and 16 vaccine candidates currently in phase III clinical trials using several platforms, such as inactivated viruses, vector viruses, and protein subunits, and mRNA. Clinical trials of the SARS-CoV-2 vaccine include a screening test consisting of thorough physical examination and laboratory tests. The safety of clinical trials is evaluated based on laboratory test results referring to the standard toxicity grading scale. Immunogenicity assessment at the stage of clinical trials of vaccines includes assessment of humoral and cellular immunogenicity. The humoral immunogenicity test measures the ability of antibodies to neutralize the virus with the live virus neutralization test, Pseudo Virus Neutralization Test (pVNT), and Surrogate Virus Neutralization Test (sVNT) method. The cellular immunogenicity response aims to assess the immune response that leads to the Th1-cell phenotype. The COVID-19 vaccine under development is expected to trigger a helper 1 (Th1) cell response. Th1-producing Interferon-g (IFNg) is formed during acute viral infection, and Th1-type immune response correlates with milder disease. This is one of the considerations in vaccination. Th1-cell phenotype as part of cellular immunogenicity can be evaluated with ELISPOT, interferon-gamma release assay, and flow cytometry using blood samples that have been cultured with the administration of specific SARS-CoV-2 peptides. This literature review aims to study various immunogenicity assessments in the laboratory for clinical trials of COVID-19 vaccines.